DNA-Adducts in Subjects Exposed to Urban Air Pollution by Benzene and Polycyclic Aromatic Hydrocarbons (PAHs) in Cotonou, Benin - AYI-FANOU, Lucie; AVOGBE, PATRICE HODONOU; Fayomi, Benjamin; Keith, Gerard; Hountondji, Codjo; Creppy, Edmond (My University, 2011)
Air pollution effect on humans represents a major public health problem. Exposure to genotoxic compounds in the ambient air is evaluated using different biomarkers. In the present study we assessed DNA-adducts levels in apparently healthy people living and working in the city of Cotonou (Benin) in which exposure to air pollutants such as benzene and polycyclic aromatic hydrocarbons (PAHs) mainly benzo(a)pyrene has been evidenced. Rural inhabitants were enrolled as control group. Taxi-motor- bike drivers, street food vendors, and gasoline salesmen were recruited in Cotonou whereas suburban residents were recruited in Godomey, 12 km from Cotonou. We found that taxi-motorbike drivers, road- side residents, street vendors, taxi-motor-bike drivers and gasoline sellers had significantly higher levels of DNA-adducts than suburban and village inhabitants (P \ 0.001; post hoc, LSD). Means values were 24.6 6 6.4, 23.78 6 6.9, 34.7 6 9.8, and 37.2 6 8.1 in the exposed groups versus 2.1 6 0.6 and 3.1 6 0.8 adducts/108 nucleotides, in the two control groups, respectively. We did not find any significant difference within the high exposure groups and inside low exposure subgroups (namely suburban residents and vil- lagers) because the mean individual exposure values to both PAHs and benzene were similar among sub- jects exposed in the city of Cotonou and those in suburban and village areas. However, there is significant interindividual variations in adducts levels that may reflect variation of genetic susceptibility factors. Ranges of adduct level/108 nucleotides were: 1–69, 1–76, 3–169, 4–124, 0–9, 0–8 adducts/108 for taxi- motorbike drivers, roadside residents, street vendors, gasoline sellers, suburban and village inhabitants, respectively. Our study demonstrated a clear-cut elevated level of DNA adducts in city residents than in none exposed people (or very low exposure levels people) and designate these city residents groups as people at risks for the chronic diseases possibly caused by benzene and PAHs.
Keywords: air pollution; PAHs; benzene; exposed and none exposed subjects; DNA-adducts; 32P postlabelling